Психологічні типи як інструмент підвищення мотивації та командної ефективності - Ніколаєва, М. А.; Nikolaieva, M.; Насад, Неоніла Вікторівна; Nasad, N. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: В сучасному менеджменті аналіз психологічних типологій стає надзвичайно важливим, оскільки дозволяє краще розуміти особистісні особливості працівників та їхній внесок у формування динаміки команди. Ціль дослідження полягає у вивченні провідних класифікацій психологічних типів, зокрема систем MBTI та DISC, а також у визначенні їхнього впливу на управлінські процеси, процес прийняття рішень і створення команд. Отримані дані демонструють, що окремі типи особистості різним чином обробляють інформацію, спілкуються між собою та реагують на мотиваційні стимули, що безпосередньо впливає на продуктивність. Виявлено, що суміш різних типологічних профілів у колективі стимулює підвищення креативності, посилює адаптивність компанії і підвищує ефективність взаємодії в команді. На підставі дослідження зроблено висновок, що застосування психологічної типології може слугувати ефективним засобом оптимізації управлінських рішень, підвищення продуктивності співробітників і створення згуртованих, високоефективних команд. /// EN: The study examines the role of psychological types in modern management, emphasizing their influence on employee motivation, team interaction, and management decisions. Integrating the Myers-Briggs Type Indicator (MBTI) and DISC (Dominance, Influence, Steadiness, Compliance) models, the work provides a comprehensive analysis of personality traits, identifying characteristic patterns of perception, communication, and behavior that affect workplace performance. The data collected through a structured survey demonstrates how different psychological types respond to leadership styles, cope with conflicts, and engage in collective tasks. The results show that employees with complementary traits increase team cohesion, while mismatched profiles can make communication difficult and reduce productivity. The f indings highlight the practical potential of psychological typologies as tools for optimizing HR strategies, individualizing motivational approaches, and improving team dynamics. In addition, the study discusses implications for management practices, suggesting that understanding employees' personality profiles contributes to more effective delegation, conflict resolution, and project planning. The application of psychological knowledge allows organizations to combine individual strengths with task requirements, contributing to engagement and improving overall performance. The study also identifies prospects for further study, including the integration of psychological models into digital HR systems, the use of predictive analytics for team building, and the development of adaptive management frameworks for different employee profiles. As a result, a systematic assessment of psychological types appears as a strategic tool for improving the efficiency of the workforce, developing professional potential and forming a sustainable organizational culture. The use of psychological typologies allows managers to make informed decisions, improve motivation and achieve high team effectiveness in a dynamic and complex organizational environment.
Psychological types as a tool to increase motivation and team effectiveness
Keywords: психологічні типи; мотивація персоналу; командна ефективність; управлінські рішення; комунікація; psychological types; employee motivation; team effectiveness; managerial decision-making; communication